African American Female Trajectories of Offending From Youth to Young Adulthood. (March 2019) - Evans, Sara Z.; Abderhalden, Frances P.; Simons, Leslie G.; Simons, Ronald L.
Using data from the Family and Community Health Survey, the current study explores developmental pathways from age 11 to 24 of African American males and females. This study describes the number and type of trajectories of offending for male and female African Americans, as much research in the past on trajectories has focused on White and/or male samples. We also investigate predictors of offending for the females both between and within trajectory groups. Results indicated that females who experienced higher levels of racial discrimination and greater parental hostility were more likely to be in a late bloomer group, compared with the low-level group. In addition, higher levels of racial discrimination and deviant peer affiliation were predictive of more offending.